Democracy and Technocracy in Sweden's Experience of the COVID-19 Pandemic - Andersson, Staffan; Aylott, Nicholas; Eriksson, Johan (Frontiers in Political Science, 2022)
Sweden's management of the coronavirus pandemic, beginning in early 2020, has been much discussed because it deviated from other countries' equivalents. Set in the context of scholarly debate about the balance between politicians and experts in political decision-making, we argue that a necessary condition for this case of Swedish exceptionalism was the manner of policy-making adopted by the Swedish authorities. In this article, we describe this policy-making procedure, which involved a radical form of delegation by elected politicians to appointed experts, and seek to explain how it came about. We focus on the 1st year of the pandemic, and use media reports and other public documents, including parts of a public inquiry, as our empirical material.